Interpersonal communication relating to others - Beebe, Steven A., 1950-; Beebe, Susan J.; Redmond, Mark V., 1949- (2018)
"It's about how to enhance the quality of your interpersonal communication with others. The importance of being other-oriented was the foundation of the first eight well- received editions of Interpersonal Communication: Relating to Others, and it continues to be the central theme of the ninth edition"--
Introduction to interpersonal communication -- Interpersonal communication and self -- Interpersonal communication and perception -- Interpersonal communication and diversity: adapting to others -- Listening and responding skills -- Verbal communication skills -- Nonverbal communication skills -- Conflict management skills.
Includes bibliographical references (pages 368-398) and index.
Keywords: Interpersonal communication; Large type books